The Elgar companion to the economics of property rights - Colombatto, Enrico (Cheltenham, UK ; Norhthampton, MA, USA : Edward Elgar, 2004)
Illuminating the major accomplishments of the economics of property rights, this volume features 22 chapters written by contributors from around the world.
Includes bibliographical references and index.
aia 30/08/16
Loan
Keywords: Property; Right of property